Improving Oral Bioavailability of Agaricoglycerides by Solid Lipid-Based Self-Emulsifying Drug Delivery System - Chun Chao Han, Linna Han (Journal of Applied Pharmaceutical Science)
Agaricoglyceride A (AGA), showed strong activities against neurolysin. The objectives of this study was to prepare solid self-emulsifying drug delivery system (sSEDDS) by spray drying the SEDDS (liquid system) using Aerosil 200 as the inert solid carrier, and to evaluate the enhanced bioavailability (BA) of AGA from sSEDDS. The AGA formulated in the sSEDDS was quickly and completely dissolved within 20min, both in 0.1N HCl and phosphate buffer pH 6.8 dissolution media, whereas AGA powder was significantly less dissoluble. Meanwhile, the sSEDDS formulation was stable for at least 90days at room temperature. the plasma levels of AGA in the solid SEDDS group at the dose level (15mg/kg) remained detectable for up to 1.5 h after the oral dose. After oral administration to rats, a significant increase (P
Keywords: Cefpodoxime Proxetil, swelling index, floating capacity, Guargum, HPMC, Carbopol 934P